Equivalence of trophic structure between a tropical and temperate mangrove ecosystem in the Indo-Pacific - Mazumder, Debashish; Saintilan, Neil; Md. Yusoff, Fatimah; Kelleway, Jeffrey J. (C S I R O Publishing, 2019)
In this study we compared ecosystem trophic structure between a tropical mangrove forest at Matang, Malaysia, and a temperate mangrove forest near mangrove poleward limits at Towra Point in south-east Australia. These forests are separated by 8500 km of ocean over 45° of latitude and are of contrasting size, productivity and diversity. However, we observed a marked degree of similarity in food chain length (approximately four trophic levels in both forests), the taxonomy of key intermediate members of the food chain and the isotope signature of primary carbon sources, suggesting a strong contribution of surface organic matter rather than mangrove detritus. Common families were represented among dominant grazing herbivores, zooplanktivorous fishes, decapod crustaceans and top predators. These similarities suggest that there is some consistency in trophic interactions within two mangroves on opposite sides of the Indo-Pacific, despite a degree of evolutionary divergence in the assemblage.